2014
DOI: 10.1103/physrevlett.112.193902
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Migrating Transverse Anderson Localizations of Light in Nonlocal Media

Abstract: We report the experimental observation of the interaction and attraction of many localized modes in a two-dimensional system realized by a disordered optical fiber supporting transverse Anderson localization. We show that a nonlocal optically nonlinear response of thermal origin alters the localization length by an amount determined by the optical power and also induces an action at a distance between the localized modes and their spatial migration. Evidence of a collective and strongly interacting regime is g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
(55 reference statements)
0
35
0
Order By: Relevance
“…Moreover, modeling spatial solitons in the highly nonlocal limit leads to the concept of accessible solitons [16], a useful approximation in various instances [17][18][19]. Nonlocality in optics also plays an important role in photon condensation [20], dispersive shock waves [21][22][23], distributed coupling to guided waves [24,25], gradient catastrophe [26], and Anderson localization [27].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, modeling spatial solitons in the highly nonlocal limit leads to the concept of accessible solitons [16], a useful approximation in various instances [17][18][19]. Nonlocality in optics also plays an important role in photon condensation [20], dispersive shock waves [21][22][23], distributed coupling to guided waves [24,25], gradient catastrophe [26], and Anderson localization [27].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Karbasi, et al reported the first observation of TAL in disordered optical fibers [13][14][15]. The disordered optical fibers have since been used for high-quality image transport [22][23][24][25][26], beam multiplexing [27], wave-front shaping and sharp focusing [28][29][30], nonlocal nonlinearity [31,32], single-photon data packing [33], optical diagnostics [34], and random lasers [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…In order to check, whether this behaviour predicted by the PT theory is realistic, we have taken samples composed of microfibres with different permittivity (polystyrene, PS ǫ PS /ǫ 0 = 1.59, polymethylmethacrylate, PMMA, ǫ PMMA /ǫ 0 = 1.49), fabricated as described in 27 in which transverse localization is observed 27,[31][32][33] . We measured the localization length in such devices by injecting a focused (order of a micrometer) monocromatic light at the fibre input tip while monitoring the total fibre output.…”
mentioning
confidence: 99%